Word – Sign – Meme - Хайдер, Тетяна Василівна (Київського національного університету імені Тараса Шевченка, 2025)
The article examines the Internet meme as a pragmalinguistic and multimodal phenomenon that combines verbal, visual, and intertextual elements. Integrating semiotic resources such as the mode, media, and meaning potential of memes to help readers understand the background knowledge about memes. Memes function as speech acts. While it is possible that all types of memes can be considered speech acts, some types of memes are more accessible to construction than others and are also used more frequently. It demonstrates that memes are grounded in precedent phenomena—names, expressions, events, and cultural images—that acquire satirical, ironic, or mobilizing meanings in new contexts. During the war in Ukraine, memes are used deeply and deeply as a way of emotional support, relieving anxiety and building resilience (“emotional therapy”). In these cases, word → associative → meme: language creates a “semantic explosion”, which, through media repetition and variability, is formed into a stable cultural sign. In this context, the active inclusion of the Polish media space in the orbit of Ukraine’s allies in the confrontation with Russia is an extremely important stage. In crisis contexts (war, pandemic), memes are transformed from entertainment content into a tool of collective mobilization. Based on Ukrainian and Polish media materials (e.g., Putler, Bavovna, Russian warship, go…, Denaturatow, Dziś kijek), the study shows that memes function as speech acts: the illocutionary phase is realized through satire, euphemization, or political commentary, while the perlocutionary phase lies in influencing public opinion and shaping collective identity. Special attention is given to the multimodal nature of memes, which enables the integration of text, images, and cultural allusions into a unified communicative act. The article also highlights the challenges of translation and transcultural adaptation, since memes may lose their illocutionary force when transferred across linguistic and cultural communities.

У статті розглянуто інтернет-мем як лінгвопрагматичний феномен, що виникає на основі прецедентних імен, висловів, подій та культурних образів й поєднує вербальні, візуальні та інтертекстуальні елементи. Показано, що основою мему є прецедентні імена, вислови, події та культурні образи, які в новому контексті набувають сатиричного, іронічного чи мобілізаційного змісту Здійснено порівняльний аналіз українського та польського медійного дискурсу, зокрема в контексті війни Росії проти України. Представлено, що меми функціонують як мовленнєві акти, де ілокутивна фаза реалізується через сатиру, сарказм, евфемізацію або політичний коментар, а перлокутивна – у впливі на громадську думку, формуванні колективної ідентичності та політичної мобілізації ілокутивна фаза реалізується у формі сатири, евфемізації чи політичного коментаря, тоді як перлокутивна полягає у впливі на громадську думку та формуванні колективної ідентичності. Особливу увагу приділено мультимодальній природі мемів, яка дозволяє поєднувати текст, зображення та культурні алюзії в єдиному комунікативному акті. На матеріалі українських та польських медіа (зокрема, приклади «Путлер», «Бавовна», «Русскій воєнний корабль, іди…», «Denaturatow», «Dziś kijek») виявлено, що в обох культурах меми є реакцією на прецедентні реалії – постаті, події та висловлювання, які вже стали знаковими в масовій свідомості й отримали нове життя у вигляді цифрових об- разів. Зроблено висновок про необхідність подальшого дослідження проблем перекладу та транскультурної адаптації мемів, що зберігають або втрачають свою ілокутивну силу при інтерпретації різними аудиторіями. Наголошено на необхідності подальших досліджень проблем перекладу й транскультурної адаптації, оскільки меми можуть втрачати ілокутивну силу при перенесенні між мовними та культурними спільнотами.
Слово – знак – мем
Keywords: Internet meme; multimodality; precedent phenomena; pragmalinguistics; speech act; Ukrainian and Polish media discourse; інтернет-мем; мультимодальність; прецедентні феномени; прагмалінгвістика; мовленнєвий акт; український та польський медійний дискурс